A Comparison of the Policies in Taiwan and South Korea for Developing a “World-Class University” and their Outcomes - Wang, Ru-Jer; Huang, Yueh-Chun (Advances in Social Sciences Research Journal, 2018)
In recent decades numerous nations around the world have been making major efforts in developing so-called “world-class universities,” and Taiwan and South Korea are no exceptions. During the past ten years Taiwan adopted its “Five Year-50 Billion Excellence Initiative,” and South Korea has implemented BK21 PLUS. In this paper we examine and compare the relevant policies affecting the development of world-class universities in Taiwan and South Korea. The purposes of this study are: 1) to review the backgrounds behind the policies in Taiwan and South Korea relating to the development of world-class universities; 2) to present an overview of the relevant policies in Taiwan and South Korea; 3) to examine and compare the outcomes of these polices; and 4) to provide suggestions based on the findings of this study. The methods employed in this study include documentary and secondary data analysis and comparative study. The main findings were as follows: 1) additional expenditures have produced additional outcomes; 2) when examining the outcome of a particular policy, it is necessary to pay attention to unexpected effects; 3) when examining policy effects, it is necessary to take into account a diverse range of evidence; and 4) there is no magic prescription for developing a world-class university.